2004
DOI: 10.1634/stemcells.22-4-531
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Transfection of Embryonic and Adult Stem Cells

Abstract: The ability of embryonic stem cells and adult stem cells to differentiate into specific cell types holds immense potential for therapeutic use in cell and gene therapy. Realization of this potential depends on efficient and optimized protocols for genetic manipulation of stem cells. In the study reported here, we demonstrate the use of nucleofection as a method to introduce plasmid DNA into embryonic and adult stem cells with significantly greater efficiency than electroporation or lipid-based transfection met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
127
3
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(146 citation statements)
references
References 33 publications
12
127
3
4
Order By: Relevance
“…The rate of plasmid transfection in hMSCs was in line with the most previous reports (Peister et al 2004;Falk et al 2002;Lakshmipathy et al 2004;Weissinger et al 2003) while Hoelters et al (2005) reported higher transfection efficiency. Our lower yield could be because of the difference in methods for determination of transfection efficiency, which was fluorescence microscopy and Neubauer chamber in their study and flow cytometry in ours.…”
Section: Discussionsupporting
confidence: 91%
“…The rate of plasmid transfection in hMSCs was in line with the most previous reports (Peister et al 2004;Falk et al 2002;Lakshmipathy et al 2004;Weissinger et al 2003) while Hoelters et al (2005) reported higher transfection efficiency. Our lower yield could be because of the difference in methods for determination of transfection efficiency, which was fluorescence microscopy and Neubauer chamber in their study and flow cytometry in ours.…”
Section: Discussionsupporting
confidence: 91%
“…(ii) the specifics of construct and driving promoters [36][37][38][39][40][41] , as well as (iii) the transfection method employed and the resulting integration sites [42][43][44][45] . Single-cell RT-PCR analysis as well as post hoc immunohistochemistry could be used to exclude subpopulation analysis and to demonstrate additional features of recorded cells.…”
Section: Problem Possible Reason Solutionmentioning
confidence: 99%
“…Gonzales et al [61] simplified the protocol by the delivery of "all-inone" single plasmid containing all the four reprogramming factors, using nucleofection transfection technology. Nucleofection is a proprietary technology provided by Amaxa [Cologne, Germany] based on electroporation technique that combines specific cell-type solutions with specific electrical parameters generated by the Nucleofector™ device to deliver DNA directly to the nucleus, which may consequently lead to enhanced gene expression [62]. Unlike the serial transfection procedure by Okita et al [60], the iPS cells generated using nucleofection did not show evidence of transgene insertion in their genome.…”
Section: Non-viral Delivery Systemmentioning
confidence: 99%